DISCOURSE MARKERS IN TALK SHOWS: THE CASE STUDY OF THE TONIGHT SHOW STARRING JIMMY FALLON - Ni Luh Wanda Kumala Dewi; Putu Nur Ayomi (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2024)
This research aimed to determine what type and function of discourse markers occur in spoken language, especially in public informal conversation, using Fraser's (2009) theory. The data was taken from a popular talk show entitled 'The Tonight Show Starring Jimmy Falon.' This research uses a descriptive qualitative method with five chosen episodes of 'The Tonight Show Starring Jimmy Falon' from February to April 2023. Based on the findings, four types of discourse markers and six functions of discourse markers were found in the data. The most used discourse markers were elaborative, and the most used function was to denote additive information or ideas. In contrast, inferential markers were the most infrequently used discourse marker in the data. Moreover, the most infrequent function of discourse markers found in the data was to conclude information or ideas since this shows belongs to light entertainment.